2015
DOI: 10.1149/06438.0013ecst
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride Materials for Energy Applications

Abstract: Polymeric layered carbon nitrides were investigated for use as catalyst support materials for proton exchange membrane fuel cells (PEMFCs) and water electrolyzers (PEMWEs). Three different carbon nitride materials were prepared: a heptazine-based graphitic carbon nitride material (gCNM), poly (triazine) imide carbon nitride intercalated with LiCl component (PTI-Li+Cl-) and boron-doped graphitic carbon nitride (B-gCNM). Following accelerated corrosion testing, all graphitic carbon nitride materials were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…The observed asymmetry of the low-frequency peak could be due to structural inhomogeneity as well as the effect of 13 C, 14 N residual dipolar couplings, that are known to be significant at a relatively low magnetic field of 7.05 T. [40] In the single-pulse MAS experiment, which is better suited for quantitative estimates than CP-MAS, the shoulder at δ = 151 ppm is significantly smaller ( Figure S3a In their study of TGCN, Algara-Siller et al observed a broad resonance spanning a similar range (145-172 ppm with a maximum near 160 ppm) to that observed for the Pharaoh's serpent material [13] ( Figure S4, Supporting Information). Although their sample was nominally H-free, both 1 Figure S5, Supporting Information), [36] similar to those observed for the Pharaoh's serpent. The related crystalline compound PTI·LiCl also showed three peaks at 168, 162.6, and 157.9 ppm with relative intensities that evolved as a function of CP-MAS NMR contact times.…”
Section: Articlesupporting
confidence: 59%
“…The observed asymmetry of the low-frequency peak could be due to structural inhomogeneity as well as the effect of 13 C, 14 N residual dipolar couplings, that are known to be significant at a relatively low magnetic field of 7.05 T. [40] In the single-pulse MAS experiment, which is better suited for quantitative estimates than CP-MAS, the shoulder at δ = 151 ppm is significantly smaller ( Figure S3a In their study of TGCN, Algara-Siller et al observed a broad resonance spanning a similar range (145-172 ppm with a maximum near 160 ppm) to that observed for the Pharaoh's serpent material [13] ( Figure S4, Supporting Information). Although their sample was nominally H-free, both 1 Figure S5, Supporting Information), [36] similar to those observed for the Pharaoh's serpent. The related crystalline compound PTI·LiCl also showed three peaks at 168, 162.6, and 157.9 ppm with relative intensities that evolved as a function of CP-MAS NMR contact times.…”
Section: Articlesupporting
confidence: 59%
“…These mechanically produced composites did not exhibit competitive electrocatalytic (EC) performance when tested as anodes in a PEMWE cell, displaying a potential of 2.30 V at 0.42 A cm −2 , for a gCNH-IrO 2 (40%) composite compared with 1.85 V obtained for IrO 2 NPs at the same current density. However, electrochemical impedance measurements did indicate that the gCNH-IrO 2 composites showed enhanced charge transfer kinetics as the current density was increased, thus, suggesting ways to improve the EC performance [41]. Our results indicated that by developing a method to obtain a better distribution of the IrO 2 nanoparticles onto the gCNH substrate, a high-performance EC anode behavior could be obtained.…”
Section: Resultsmentioning
confidence: 86%
“…In a previous preliminary study, we had reported the preparation of gCNH-nano-IrO 2 composites by ball-milling mixtures of the two individual components together in isopropanol [41]. These mechanically produced composites did not exhibit competitive electrocatalytic (EC) performance when tested as anodes in a PEMWE cell, displaying a potential of 2.30 V at 0.42 A cm −2 , for a gCNH-IrO 2 (40%) composite compared with 1.85 V obtained for IrO 2 NPs at the same current density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all Pt supported on 3D aerogel materials are still significantly poorer than commercial Pt/C, with open circuit voltages (OCVs) at least 130 mV lower. Note that the performance of Pt/rGO is lower than that reported in the literature for in-situ PEM fuel cells (53), meaning that there is still scope for improvement in terms of aerogel pore size, ink formulation and electrode fabrication. Pt supported on bulk PTI is not shown, as the conductivity and surface area are too low to work in fuel cells.…”
Section: Fuel Cell Testingmentioning
confidence: 80%